2004
DOI: 10.1128/jvi.78.4.1623-1635.2004
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Effects of 2-Bromo-5,6-Dichloro-1-β- d -Ribofuranosyl Benzimidazole Riboside on the Genome Structure, Packaging, and Egress of Guinea Pig Cytomegalovirus

Abstract: The halogenated benzimidazoles BDCRB (2-bromo-5,6-dichloro-1-␤-D-riborfuranosyl benzimidazole riboside) and TCRB (2,5,6-trichloro-1-␤-D-riborfuranosyl benzimidazole riboside) were the first compounds shown to inhibit cleavage and packaging of herpesvirus genomes. Both inhibit the formation of unit length human cytomegalovirus (HCMV) genomes by a poorly understood mechanism (M. R. Underwood et al., J. Virol. 72:717-715, 1998; P. M. Krosky et al., J. Virol. 72:4721-4728, 1998). Because the simple genome structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 68 publications
3
21
0
Order By: Relevance
“…The addition of inhibitors of DNA, RNA, and protein synthesis during this time window permitted evaluation of their effects specifically on genome maturation. In addition, analysis of terminal structures on HCMV replicative intermediates revealed striking similarities to effects previously observed during BDCRB treatment of GPCMV (43).…”
supporting
confidence: 72%
“…The addition of inhibitors of DNA, RNA, and protein synthesis during this time window permitted evaluation of their effects specifically on genome maturation. In addition, analysis of terminal structures on HCMV replicative intermediates revealed striking similarities to effects previously observed during BDCRB treatment of GPCMV (43).…”
supporting
confidence: 72%
“…8). Lower-molecular-weight smears of viral DNA were detected in samples from all four viruses and appeared similar to those observed previously for human cytomegalovirus (HCMV) (18) and guinea pig cytomegalovirus (24). Within these smears, no distinct 191-or 45-kb species could be distinguished, nor were differences evident between viruses containing functional or nonfunctional cleavage sites.…”
Section: Vol 82 2008 Cis-acting Sequences In Herpesvirus Genome Matsupporting
confidence: 54%
“…However, other studies suggest that pac2 or adjacent sequences may direct the initiation of DNA packaging, perhaps by binding proteins that mediate docking to procapsid portals, and that pac1 and pac2 independently govern formation of their respective termini (13,22,26,30). In addition, terminal sequences have been implicated as having a role in the duplication of terminal repeats (21) and in postpackaging capsid maturation events, such as the sealing or stabilization of DNAcontaining capsids or their targeting for nuclear egress (13,24). Indeed, using an HSV-1 amplicon system, Hodge et al found that mutation of pac1 sequences did not prevent packaging of DNA into intracellular capsids but rather gave rise to packaged amplicon genomes that appeared normal at their Uc (pac2) ends but lacked Ub (pac1) ends.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is not consistent with the assumption that AIC246 treatment results in concatemers remaining uncut and not being encapsidated. Recent findings of McVoy and Nixon may offer an explanation for this phenomenon (36,39). While analyzing the effect of BDCRB on HCMV genome maturation, the authors confirmed that BDCRB predominantly acts via blocking the processing of viral concatemer DNA to monomeric genome lengths (36,48).…”
Section: Discussionmentioning
confidence: 74%